Pemanfaatan Platform Merdeka Mengajar (PMM) dalam Pengembangan Profesionalisme Guru secara Berkelanjutan - LATIP, ABDUL; ANGGA SAPUTRA, FRASETYO; USMAN, ALIA; MUNIM AL BASMELAH, ABDUL; WAHYU PRATOMO, HERDIANTO (Universitas Insan Budi Utomo, 2024)
This research aims to describe the use of the platform merdeka mengajar (PMM) and its impact on teacher professionalism. This research uses a literature review with the narrative literature review (NLR) type, which consists of four stages, namely determining the study topic, searching and selecting sources, analyzing and synthesizing sources, and choosing the narrative structure. The NLR results show that 1) the independent teaching platform has 5 features that teachers can use to increase competence and professionalism in carrying out their duties. The five features of PMM are inspirational videos, independent training, proof of work, student assessments, and teaching tools. 2) Teachers already use the features in PMM. The use of PMM has an impact on teachers, namely building a collaboration space for teachers to improve their competence, making it easier for teachers to choose and design learning that suits students' needs and characteristics, making it easier for teachers to make appropriate and appropriate assessments for students, and has an impact on teacher competence. Comprehensively and sustainably. Based on this, the independent teaching platform is an important platform for increasing teacher professionalism with features that are productive and collaborative.